Mobile Wheeled Robot Motion Control with Usage of Geolocation Sensors - Bezmen, P.; Tuladhar, D. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
The authors state mobile robot motion control peculiarities induced by the operation of geolocation sensors. This paper specifies features of geolocation sensors – GPS receiver and electronic compass (magnetometer). The lay of the land and man-made structures are obstacles for GPS signals. The paper describes the precision of the GPS receiver and offers a method that can reduce the probable error of the GPS signal. This method is a program digital filter based on finding GPS data kernel – the most likely mobile robot location, expressed in terms of latitude and longitude. The paper formulates functioning principles of the six-wheeled robot movement automatic control system that uses geolocation sensors data.